2018
DOI: 10.11113/jt.v80.10489
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Maximum Speed Limit in Urban Road to Increase Traffic Safety

Abstract: Speed is one of the main risk factors in road traffic safety and become a traffic problem in developing countries. Three factors that cause accidents are human factor, vehicle, and environment. Speeding is one of the main cause factors in traffic accident. Traffic speed must be limited adjust with the activities in the street and potential accident. The aim of this research is to determine the maximum speed limit in urban road to increase traffic safety and to analyze the percentage of vehicle exceeding speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 12 publications
(14 reference statements)
1
11
0
2
Order By: Relevance
“…Sugiyanto et al conducted a study on the effect of speed limit signs, and the results showed that the installation of speed limit signs on the highway is less effective to reduce vehicle speed. After the speed limit sign is installed, the vehicle speed is reduced only about 2.9 km/h to 5.5 km/h (5.6 to 10.1%) [37]. e speed limit studied in this paper is 80 km/h and 120 km/h.…”
Section: Resultsmentioning
confidence: 93%
“…Sugiyanto et al conducted a study on the effect of speed limit signs, and the results showed that the installation of speed limit signs on the highway is less effective to reduce vehicle speed. After the speed limit sign is installed, the vehicle speed is reduced only about 2.9 km/h to 5.5 km/h (5.6 to 10.1%) [37]. e speed limit studied in this paper is 80 km/h and 120 km/h.…”
Section: Resultsmentioning
confidence: 93%
“…According to the study, this led to a 41.9% decline in the number of road accidents, based on the number of road casualties at that time [22]. Recent studies, such as Aldred (2019) or Sugiyanto (2018), also take up this argument of increased safety at lower speeds in further analyses [23,24].…”
Section: Financial Incentivesmentioning
confidence: 98%
“…Angka kecelakaan dan jumlah korban kecelakaan lalu lintas di Indonesia masih tinggi. Angka kecelakaan lalu lintas semakin meningkat seiring dengan bertambahnya jumlah kendaraan khususnya sepeda motor dan mengendarai kendaraan melebihi batas kecepatan maksimum yang diijinkan atau speeding Sugiyanto & Malkhamah, 2018;Sugiyanto et al, 2019a Metrics and Evaluation, 2018). Tiga faktor penyebab kecelakaan lalu lintas yaitu manusia, kendaraan, dan lingkungan (Sugiyanto & Santi, 2015).…”
Section: Pendahuluanunclassified